TRANSFORMASI DANA BERGULIR MASYARAKAT EKS PNPM MENJADI BADAN USAHA MILIK DESA BERSAMA (BUMDESMA) MENURUT PERATURAN PEMERINTAH NOMOR 11 TAHUN 2021 - Rino Setiady; Wendra Yunaldi; Erry Gusman (Ensiklopedia of Journal, 2023)
Formation of community activity managers of the former national program for rural independent community empowerment into joint village-owned enterprises. To what extent is the effectiveness of the technical guidelines for the formation of joint village-owned enterprises (BUMN Desma) from the community revolving fund activity manager of the former national program for rural independent community empowerment (PNPM Mpd) in its implementation. The results of this study indicate that local governments have not utilized regional autonomy as widely as possible as explained in Law No. 23 of 2014 concerning Regional Government, as evidenced by the absence of appeals or regulations from both provincial and district governments. The elements involved in carrying out their roles according to their respective duties and functions based on the Letter of the Directorate General of Economic Development and Investment for Villages, Disadvantaged Areas, and Transmigration, Number 191/PRI.02/IV/2022 Dated April 06, 2022. There is no common understanding regarding regulations ranging from Law no 11 of 2020 concerning Job Creation, Government Regulation number 11 of 2021 concerning BUM Desa, Regulation of the Minister of Villages, Development of Disadvantaged Regions and Transmigration number 15 of 2021 concerning Procedures for the Establishment of Community Revolving Fund Activity Managers of the National Program for Rural Independent Community Empowerment into Joint Village-Owned Enterprises and Directorate General Letter of Economic Development and Investment for Villages.